Right and left ventricular adaptation to regular physical activity in elite male athletes - Major, Z.; Kneffel, Z.; Csajagi, E.; Toth, M.; Pavlik, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The athlete`s heart undergoes morphological and functional changes as a result of regular physical activity. Left ventricular dimensions, wall thicknesses and function are echocardiographic measurements widely used in research, but the functional adaptation of the right ventricle remains unknown. The aim of this study was to assess left and right ventricular function and enlargement in elte athletes and in healthy sedentary non-athletes. Methods The study population consisted of 20 elite highly-trained male athletes and 15 age-matched normotensive healthy non-athletes. In addiction, left and right ventricular systolic (S`) and diastolic functions (E peak, A peak, E/A ratio, E`, A` velocities and E`/A` ratio) were determined by conventional PW Doppler echocardiography and Pulsed wave Tissue Doppler imaging at the septal and lateral corners of the mitral and tricuspid annulus. Tricuspid and mitral inflow velocities were obtained in a four-chamber view by placing a cursor at the tips of the mitral and tricuspid valve. Right and left ventricular longitudinal diameters were also determined. Measurements represent the average of three cycles. Comparisons among data were performed with Student`s test. Results The athletes and members of the control group did not differ significantly in mean body surface area (p<0,3). The group of athletes showed highly but not statictically significant velocity of mitral and tricuspid E (p<0,5; p<0,6) wave, and the tricuspid E/A (p<0,4) ratio than non-athletes. Mitral and tricuspid annulus Am (both p<0,005), and Aa (p<0,0001 and p<0,001) were significantly smaller in athletes than in non-athletes. E/Em ratio on the right side (p<0,05) was also significantly less in athlete`s group than in controls. Em/Am ratio (both p<0,05), and Ea/Aa on either side (p< 0,001 and p<0,005) were significantly higher in athletes than in sedentary controls. In the group of non-athletes and in the competitors of several kind of sport the right ventricular systolic function was not statictically significant, although, we found significant difference between the two groups in the left ventricular dimensions (p<0,05). In the end-diastolic dimension of the right ventricle between the two groups proved to be significant as well (p<0,05). Discussion Regular and extensive training results in similar changes in right ventricular function to that of the left ventricle.